Wealth ranking and livelihood analysis for microwatershed development - G Nirmala; Kausalya Ramachandran; UK Mandal; V Ramesh; G. Ramesh (Journal of Agricultural Extension Management, 2025)
Integrated watershed management is an interdisciplinary approach aiming at rational utilization of natural resources while achieving equity in socio economic development of all sections of the community for increasing productivity of dry lands on a sustainable basis. (HP Singh and T K Bhati 1993). Emphasis has been laid upon the socio economic status of poor on par with rich in watershed development under OPAP programs of Ministry of Rural development .The study was aimed at assessing the real poor and livelihood patterns of all economic groups through PRA techniques of wealth ranking and livelihood analysis